Estudio bioclimático de la vivienda shuar como resultado del uso de nuevos materiales, en el cantón Morona. - Alarcon Rivadeneira, Pablo Gabriel (2019)
The way of life of the Shuar people has been affected due to the transformation of their houses; this has generated problems of health and stability creating unworthy spaces and affecting the quality of life, thus there was the need to carry out the project of the bioclimatic study of the current housing of de Shuar people. Getting to know the existing housing and its transformation at present, through climate simulation software which helps understand the behavior inside the house and see what the degree of comfort is. Through a proposal adapted to the humid warm climate of don Bosco parish in Seville, which started front the study of the current houses based on criteria, concepts and bioclimatic strategies in order to create a decent space whit thermal comfort without affecting their environment. Therefore, a formal functional and technological solution has been present to achieve a total thermal comfort.